Design and Development an Augmented Reality Pop-Up Earth Application Using the Design Thinking Method - Sari, Nandha Mustika; Ashar, Muhammad; Kirana, Kartika Candra; Rahmadya, Budi (Universitas Negeri Malang, 2022)
The importance of providing information about planet earth to users is one of the reasons for conducting this research, because humans are living beings who play an important role in protecting the earth so that various information and knowledge about planet earth are needed. To get this information, the smartphone is one of the tools used as a medium of information. Through the use of this technology, researchers convey information using an interactive pop-up application in the form of three dimensions. To realize the interactive application, researchers use markerless-based augmented reality technology, so that users can use it without any limitations of space and time.The development method used in this research is the design thinking method consisting of 5 stages, namely empathize, define, ideate, prototype, and test. The testing phase in this study uses blackbox testing, validation tests carried out by experts, and a usability scale system carried out by potential users to determine the level of satisfaction when using the application. The results of the Pop-Up Earth application test show that the application is in grade A or the excellent category with an average SUS score of 82.5% and can run well as expected. Experts state that this application is valid for use with an average value of 98.3% for the delivery of application media and 87.5% for the delivery of application information. It is hoped that the Pop-Up Earth application can provide various information about planet earth to users interactively and informatively.